God Does Not Play Dice, but Do We? On the Determinism of Choice in Long-run Interactions - Teresa Backhaus; Yves Breitmoser (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
When do we cooperate and why? This question concerns one of the most persistent divides between ẗheory and practice\", between predictions from game theory and results from experimental studies. For about 15 years, theoretical analyses predict completely-mixed b̈ehaviors̈trategies, i.e. strategic randomization rendering ẅhenänd ẅhyq̈uestions largely moot, while experimental analyses seem to consistently identify pure strategies, suggesting long-run interactions are deterministic. Reanalyzing 145,000 decisions from infinitely repeated prisonerś dilemma experiments, and using data-mining techniques giving pure strategies the best possible chance, we conclude that subjects play semi-grim behavior strategies similar to those predicted by theory.
Keywords: C72; C73; C92; D12; 330; repeated game; behavior; tit-for-tat mixed strategy; memory; belief-free equilibrium; laboratory experiment